Perioperative Prophylactic Antibiotics in Orthopaedic Surgery - Shrestha, Bikram Prasad; Niraula, Surya Raj; Nepal, Parvin; Khanal, Guru Prasad; Karn, Navin; Chaudhary, Pashupati; Rijal, Raju; Maharjan, Rajiv (Nepal Orthopaedic Association Journal, 2013)
Introduction: In our country, various institutes have different protocols for postoperative antibiotics. Many western literature have mentioned that administration of prophylactic antibiotics for longer than 24 hours has no advantage and may actually lead to superinfection with drug-resistant organisms. Because of environmental and theater condition most of the surgeon here are very reluctant to use prophylactic antibiotics for only 24 hours. The objective of the study was to find out the effect of duration of prophylactic antibiotics on the rate of surgical site infection in clean elective orthopaedic surgeries. Methods: This was a randomized controlled trial involving 207 clean elective orthopaedic patients undergoing surgery. The patients were divided into three groups which received intravenous prophylactic antibiotics for 24 hours, 48 hours and 48 hours followed by 7 days of oral antibiotics respectively. The patients were followed up for three months postoperatively. Result: There was no significant difference in the rate of surgical site infection among the three groups. Conclusion: We conclude that there is no benefit in prolonging prophylactic antibiotics beyond 24 hours. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9318 Nepal Orthopedic Association Journal 2013 Vol.3(1): 5-10